Self-Efficacy and Acceptance of Illness Among Older Patients with Heart Failure - Urszula Religioni; Małgorzata Kupisz-Urbańska; Wiktoria Niegowska; Agnieszka Drab; Piotr Czapski; Katarzyna Januszewska-Mukarker; Jarosław Pinkas; Beata Gellert; Janusz Ostrowski; Piotr Jankowski (Behavioral Sciences)
Health beliefs, disease acceptance, and self-efficacy significantly influence patients’ behavior. This study examined factors associated with self-efficacy and illness acceptance in patients with heart failure (HF). The study, conducted from June 2022 to June 2024, included 231 patients aged ≥ 65 years hospitalized for HF. Self-efficacy and illness acceptance were assessed using the Generalized Self-Efficacy Scale (GSES) and Acceptance of Illness Scale (AIS). The median age of participants was 80 years (72–86); a total of 63.6% were women. The AIS score median was 25, indicating moderate disease acceptance, while the GSES score median was 30, reflecting relatively high self-efficacy. Lower GSES scores were associated with a history of cancer (p = 0.002) and geriatric depression (p = 0.000). Poor illness acceptance was linked to prior myocardial infarction (p = 0.020), atrial fibrillation (p = 0.008), stroke (p = 0.040), depression (p = 0.000), and frailty (p = 0.000). Frailty (OR 0.81) and cancer history (OR 3.08) independently predicted self-efficacy, while lower illness acceptance was linked to older age (OR 0.95), stressful events (OR 0.53), stroke (OR 0.26), and improved by physical activity (OR 1.22). Our results indicated that older HF patients exhibit high self-efficacy but moderate illness acceptance. Self-efficacy is influenced by frailty and cancer history, while illness acceptance by age, stress, stroke, and physical activity.